2004
DOI: 10.1021/jf0352071
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Process Stability of Purified Green Pepper (Capsicum annuum) Pectin Methylesterase

Abstract: Pectin methylesterase (PME) from green bell peppers (Capsicum annuum) was extracted and purified by affinity chromatography on a CNBr-Sepharose-PMEI column. A single protein peak with pectin methylesterase activity was observed. For the pepper PME, a biochemical characterization in terms of molar mass (MM), isoelectric points (pI), and kinetic parameters for activity and thermostability was performed. The optimum pH for PME activity at 22°C was 7.5, and its optimum temperature at neutral pH was between 52.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
4
13
1
Order By: Relevance
“…Karakus and Pekyardimci (2012) reported temperature optimum of free PME from Malatya apricot as 60°C which is in accord the one found in this study. Reported temperature optima for PMEs from different sources include 55°C for black carrot (Unal and Bellur 2009), 55°C for hawthorn (Vivar-Vera et al 2007), between 52.5 and 55.0 for green pepper (Castro et al 2004), 55°C for tomato (Van Den Broeck et al 2000), 65°C for plum (Prunus domestica) (Nunes et al 2006), which are similar to the one obtained in this study. However, higher temperature optima were reported for PME from guava, e.g.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Karakus and Pekyardimci (2012) reported temperature optimum of free PME from Malatya apricot as 60°C which is in accord the one found in this study. Reported temperature optima for PMEs from different sources include 55°C for black carrot (Unal and Bellur 2009), 55°C for hawthorn (Vivar-Vera et al 2007), between 52.5 and 55.0 for green pepper (Castro et al 2004), 55°C for tomato (Van Den Broeck et al 2000), 65°C for plum (Prunus domestica) (Nunes et al 2006), which are similar to the one obtained in this study. However, higher temperature optima were reported for PME from guava, e.g.…”
Section: Resultssupporting
confidence: 83%
“…In a study carried out by Karakus and Pekyardimci (2012) on comparison of covalent and noncovalent immobilization of pectinesterase isolated from Malatya apricot, it was found that the pH optima of covalently-immobilized and free PME were 8.0 and 9.0, respectively, which is slightly higher than the one found for Alyanak PME. Some of the reported optimum pH values for PME from different sources are 7.5 for black carrot (Daucus carota L.) (Unal and Bellur 2009), green pepper (Castro et al 2004), plum (Nunes et al 2006) and hawthorn (Vivar-Vera et al 2007), 8.0 for orange (Amaral et al 2005), 8.0 for peach (Javeri and Wicker 1991), 9.0 for guava (Carvalho et al 2009). The pH optimum of 7.5 found in this study was in accord with these values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most plant PMEs were found to be activated by NaCl. For example, a green ball pepper PME required 0.13 M NaCl for optimal activity at neutral pH or 0.4 M NaCl at acidic pH (Castro et al 2004). On the other hand, orange PME activity was not aVected by the increase in ionic strength (Savary et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…When working with purified PME, Nguyen et al 20,21) and Castro et al 22) have proposed a similar two fraction biexponential model for the mild thermal and highpressure inactivation kinetics of purified strawberry, carrot and green pepper pectin-esterase. Similar parameters between the models were found in all studies, leading to the hypothesis that the enzymes of different species might respond similarly to heat and pressure stresses.…”
mentioning
confidence: 99%